EPISTEMOLOGI PENEMUAN HUKUM NAHDLATUL âULAMA (NU) - Pelu, Ibnu Elmi A.S (Fakultas Ekonomi dan Bisnis Islam IAIN Palangka Raya, 2016)
The dynamics of the spirit of ijtihad religious organizations in Indonesia continues to run. Nahdlat al-ââUlama or NU as a religious organization initiated by KH. Hashim Ashâari, KH. Hasbullah and KH Wahab. Bisri Samsuri on January 31, 1926 in East Java also has a style and epistemology ijtihad unique to observeThis paper reveals the epistemological model of ijtihad or istinbat al-Ahkam NU. epistemology istinbat al-Ahkam NU using methods ilhaq al-masaâil bi nazairiha. Ilhaq al-masaâil bi nazairiha is to equate the law of a case that does not exist, the books of fiqh as a reference, by the law of a similar issue that has been answered by the text in these books to be based on the elements/pillars ilhaq inside it. Ilhaq epistemology is a modification of the theory of qiyas and pillars inside. Only difference, ilhaq has elements/pillars, namely mulhiq, mulhaq âalaih, mulhiq law andâ illat al-hukm. If qiyas was based on the Qurâan and Sunnah, while ilhaq resting on the books of fiqh existing mains.